1978
DOI: 10.1038/hdy.1978.1
|View full text |Cite
|
Sign up to set email alerts
|

An ecological genetic analysis of the settling behaviour of a marine polychaete:

Abstract: SUMMARYThe settling behaviour of larvae of Spirorbis borealis from several ecologically contrasting environments was analysed in terms of means and genetic variances (the latter expressed as heritability) of two components-the probability of settling when presented with a particular substrate, and the gregarious behaviour of the larvae. Larval behaviour differed markedly according to the population from which they came: animals from a sheltered tidepool prefer Ascophyllum, and are distinctly gregarious, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…To the best of our knowledge, there is currently no data to support or deny the existence of such a relationship, although other authors have shown similar differences in response time among groups of larvae, and invoked a similar relationship to account for more rapid settlement in response to certain substrata than others (e.g. Mackay & Doyle 1978). This remains a subject worthy of further attention, and as studies on the physiological basis of larval response to metamorphic cues become more sophisticated and approach the functional mechanisms by which settlement of larvae is stimulated, our understanding of data such as these will be greatly advanced (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, there is currently no data to support or deny the existence of such a relationship, although other authors have shown similar differences in response time among groups of larvae, and invoked a similar relationship to account for more rapid settlement in response to certain substrata than others (e.g. Mackay & Doyle 1978). This remains a subject worthy of further attention, and as studies on the physiological basis of larval response to metamorphic cues become more sophisticated and approach the functional mechanisms by which settlement of larvae is stimulated, our understanding of data such as these will be greatly advanced (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…and gregariously in response to conspecific juveniles, while larvae from an exposed population settled on Fucus spp. and were not gregarious (Mackay & Doyle 1978). Cyprid larvae of a specialist barnacle settled either on the exposed axial skeleton of gorgonian corals or on adult conspecifics, ensuring proximity to mates for some larvae (Gomez 1973).…”
Section: Variation In Dispersal Potential Among Sibling Larvaementioning
confidence: 99%
“…Metamorphosis of larvae of spirorbid polychaetes in response to algal substrata (Knight-Jones et al 1971, Doyle 1976, MacKay & Doyle 1978, gregarious attachment of the bryozoan Bugula neritina (Raimondi & Keough 1990) and the polychaete Hydroides dianthus (Toonen & Pawlik 1994), response of cyprids of the barnacle Semibalanus balanoides to crevices (Chabot & Bourget 1988), and sensitivity of veligers of Phestilla sibogae to a coral inducer (Hadfield 1984), all exhibit genetic variation or differences among populations suggestive of genetic variation. The environment in which larvae develop may affect the ability to detect or respond to a settlement cue.…”
Section: Introductionmentioning
confidence: 99%